Specialty construction techniques for dam and levee remediation - Bruce, Donald A. (CRC Press/Taylor & Francis Group, 2012)
Speciality Construction Techniques for Dam and Levee Remediation deals with the construction of hydraulic cut-offs in fill, soil and rock; mainly, but not exclusively, applicable to embankment dams and levees. It then outlines how to use of prestressed rock anchors to stabilize existing concrete dams and appurtenant structures. The first main chapters follow a similar format, with an outline of the means, methods, materials and properties; illustration with case histories; quality assurance and control and verification; and then a summary of lessons learned and recommendations. The remaining main chapters are more generic and provide insight on background issues, instrumentation, specifications and contracts, and overall lessons learned.